(3Yjhf GdCKQ aj afhf GdeZGRj hGdTeGFd hGdSjQs - (3eMeO Hf eMeO Hf eMeO Hf CMeO, GHf nSpqjO GdfGS, GdjYeQj GdQHYj, CHh GdaJM, aJM GdOjf,J (B734 (3g` s
(3ChdgG (B:s
(3hHYO , adeG hbaJ Ydi eG LeYg GdfGS bOjekG hMOjKkG ef GdeLGejY aj SjQ GdfHj Udi Gddg Ydjg hSde heZGRjg hCjGeg Edi ZjQ Pdc s
(3BNQgG (B:s
(3HNW LOi CHj HcQ eMeO Hf CMeO YdbgG Ydi TjNg GdCSJGP CHj Ydj YeQ Hf eMeO GdCROi Hf GdTGhjjf YfO bQGAJg GdSjQI GdgGTejI Ydjg hCKHJgG ai WQR cJGHg QMege Gddg CLeYjf s
(3hgj ef hba MSjf Hf YHOGddWja GdYeQjs
(3heYgG UaMGJ ef PcQ GdCLhHI YeG Qei Hg eMeO Hf ESMGb (B10 (3UaMGJs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B269s
Keywords: (3GdJGQjNs